Pages from an Old Volume of Life; A Collection of Essays, 1857-1881 - Holmes, Oliver Wendell, 1809-1894 (Salt Lake City, UT : Project Gutenberg, 2004)
"Pages from an Old Volume of Life; A Collection of Essays, 1857-1881" by Oliver Wendell Holmes is a collection of essays written during the mid-19th century. This work captures the author's reflections on contemporary life, war, and societal conditions, particularly as they relate to the American Civil War. Holmes explores both personal anecdotes and broader observations regarding human behavior in times of conflict, shedding light on the psychological impact of war on both soldiers and civilians. The opening of the collection begins with the essay "Bread and the Newspaper," in which Holmes draws a parallel between the ancient Roman practice of providing food and entertainment to the populace and the contemporary need for sustenance$1 (Bincluding bread and news. He discusses how the Civil War intensifies the public's desire for information and how it disrupts the usual rhythms of life and thought. Holmes illustrates a society grappling with emotional turmoil amidst a backdrop of conflict, revealing the profound impression that war has on the human psyche. The beginning of the book sets the tone for a thoughtful exploration of the effects of war, shaping a narrative that intertwines the personal with the philosophical in an engaging and relatable manner. (This is an automatically generated summary.)s
Bread and the newspaper -- My hunt after "the captain" -- The inevitable trial -- Cinders from the ashes -- The pulpit and the pew.
Release date is 2004-09-28
Produced by David Widger
Keywords: Essays